Storytelling and Narrative Techniques: Research Findings Support their Implication in any Healthcare Setting - Theodora Thomopoulou; Antigoni Fountouki; Dimitris Theofanidis; Eleni Albani; Evangelos Dousis; Eleni Evagelou and Konstantinos Petsios (Professor Despina Sapountzi-Krepia, 2024)
Storytelling and Narrative Techniques: Research Findings Support their Implication in any Healthcare Setting